Description of the female and new records of Triatoma baratai Carcavallo & Jurberg, 2000 (Hemiptera: Heteroptera: Reduviidae: Triatominae) from Mato Grosso do Sul, Brazil, with a key to the species of the Triatoma matogrossensis subcomplex - Obara, Marcos Takashi; Barata, Jose Maria Soares; Da Rosa, João Aristeu; Ceretti Jr., Walter; de Almeida, Paulo Silva; Gonçalves, Guilmara Do Amaral; Dale, Carolina; Gurgel-Gonçalves, Rodrigo (Zootaxa, 2012)
Triatoma baratai Carcavallo & Jurberg, 2000, a species similar to Triatoma williami Galvão, Souza & Lima, 1967 andbelonging to the T. matogrossensis subcomplex, was described based on a male specimen collected in a sylvatic environ-ment, near a cave, in Bonito county, Bodoquena mountain range, state of Mato Grosso do Sul, Brazil. In the present workwe describe the female of T. baratai, captured in a chicken house, in Nioaque county, state of Mato Grosso do Sul, Brazil.Furthermore, we recorded the occurrence of T. baratai in domiciles and peridomestic environment in another four munic-ipalities (Bodoquena, Bela Vista, Corumbá, and Miranda), extending its geographical distribution. Finally, we present a key to the species of the Triatoma matogrossensis subcomplex.